1996
DOI: 10.1046/j.1365-2265.1996.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgens and the menopause; a study of 40–60‐year‐old women

Abstract: A variety of factors influence androgen production in this age group. Whereas it is difficult to predict the effect of menopause on androgen levels, LH stimulation of post-menopausal interstitial cells, modulated by a variety of factors including nutrition, and smoking, are likely to be relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
1
5

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 33 publications
7
46
1
5
Order By: Relevance
“…The lower SHBG levels in the PMO group compared to the PM group are in accordance with some studies 23,26,29 , but not with others 28,30,31 . BMI and WHR were negatively correlated to SHBG and the regression analysis showed that the SHBG levels could partly be explained by the BMI and WHR.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The lower SHBG levels in the PMO group compared to the PM group are in accordance with some studies 23,26,29 , but not with others 28,30,31 . BMI and WHR were negatively correlated to SHBG and the regression analysis showed that the SHBG levels could partly be explained by the BMI and WHR.…”
Section: Discussionsupporting
confidence: 78%
“…However, two smaller studies, one prospective and one cross-sectional, found a fall or a difference in total T over the menopausal transition 26,30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Rannevik also showed a clearcut fall in SHBG concentration related to the menopause, 20 while Bancroft showed no significant change in SHBG levels in comparing pre-, peri-, and postmenopausal women. 21 It should be noted that this study may have some empirical limitations. The small sample size does not allow the creation of Gaussian curves for each decade, with ranges expressed as 72 standard deviations of mean androgen values.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent measurement of total testosterone and sex hormone-binding globulin (SHBG) concentrations may represent an alternative when no RIA for free testosterone is available. Testosterone and SHBG levels can be used to calculate the free androgen index (FAI), where FAI ¼ (testosterone nmol/l £ 100)/SHBG nmol/l (22). Importantly, estrogens increase SHBG concentrations, and thus decrease the FAI.…”
Section: Definition Of Female Androgen Deficiencymentioning
confidence: 99%